IPTEK BAGI MASYARAKAT (IbM) DESA TERONG DAN JATIMULYO DALAM PENGELOLAAN HIPERTENSI DAN DIABETES MELITUS - Dimas Adhi Pradana; Erlina Marfianti; Nita Trimulyaningsih (UII, 2018)
IbM aims to improve the management of hypertension and Diabetes mellitus (DM) through optimizing the Posbindu (Integrated Development Position) Position of Terong and Jatimulyo Villages. The target is the establishment of posbindu with adequate facilities and trained posbindu cadres. Other targets are the formation of IEC media on hypertension and DM and obtaining baseline clinical parameters data and after management for 3 months. Devotion is implemented within 8 months in fiscal year 2017 in cooperation with the government of Terong Village and Jatimulyo and coordinate with local health center that is Dlingo II Public Health Center. The first stage is cadre training and posbindu formation. The training was conducted by using the method of